(untitled) (Journal of Economic Research & Business Administration, 2016)
The article describes the main participants of the factoring operations. Disclosed are two main types of factoring, which are widespread in Kazakhstan: factoring with recourse and non-recourse factoring. Analyzed types of factoring operations risks. The author analyzes the main activities of factoring companies in terms of the need to minimize the risks. In Kazakhstan, along with banks, which are reluctant to provide factoring services, as has its own banking products, have already appeared the first specialized factoring companies. Subjects of small and medium-sized businesses with stable debit payments, interested in urgent funding cash shortages. However, factoring potential is not fully used. There are two main problems hindering the development of factoring in Kazakhstan. The first is the low awareness of the business opportunities of factoring transactions, the second – in the absence of state support. Both problems are interrelated.